Interfacial Phenomena/Capacities Beyond Conversion Reaction Occurring in Nano‐sized Transition‐Metal‐Oxide‐Based Negative Electrodes in Lithium‐Ion Batteries: A Review - Keppeler, Miriam; Srinivasan, Madhavi (ChemElectroChem, 2017)
Nano‐sized transition‐metal oxides are of topical interest in current research towards high‐capacity negative electrodes for rechargeable lithium‐ion batteries. Schematically, an interaction with Li+ through a conversion reaction is commonly accepted. However, experimentally observed capacities often significantly exceed the correlating theoretical quantity of transferred charge carriers based on the conversion reaction. The origin of the additional capacity is under intense debate, although the indispensability of interfacial phenomena and material dimensions in the nanometer regime for concrete explanations are widely observed. Scenarios associated with additional capacities are electrode/electrolyte interphases (solid‐electrolyte interphase, polymer/gel‐like film), additional Li+ accommodation through reaction with grain boundary phases in nanostructures, interfacial Li+ accommodation along with charge separation at phase boundaries, or additional Li+ uptake in unique structural architectures with high specific surface areas that often exhibit an extensive hierarchical meso‐ and/or nanoporous system. In addition, interfacial phenomena are strongly related to battery safety, and hence a topic of highest relevance. As the number of related articles has become so intense, this Review article provides an up‐to‐date summary, and a first attempt is made to systematically classify capacity profiles of nano‐sized transition‐metal oxides that exhibit additional capacities beyond the theoretical value based on the concept of conversion reaction. Not just a phase: The origin of additional capacities for nano‐sized transition‐metal oxides is a subject of intense debate. This Review provides an up‐to‐date summary with special emphasis on scenario‐based interfacial phenomena and material dimensions in the nanometer regime. In addition, a first attempt is made to systematically classify capacity profiles of nano‐sized transition‐metal oxides with additional capacity occurrences.